New Publications and Videos - Igor V. Karyakin; Elvira G. Nikolenko (Пернатые хищники и их охрана, 2021)
Belik V.P. Birds of Southern Russia: in 2 volumes: Materials for the inventory. Volume 1: Non-Passerines. Rostov-on-Don; Taganrog: Southern Federal University Press, 2021. 812 p. (ISBN 978-5-9275-3875-1). 58 fig., 5 tables, 2885 bibl.